Hide and seek: The supply and demand of information for household solar photovoltaic investment. (February 2022) - Sommerfeldt, Nelson; Lemoine, Ida; Madani, Hatef
Abstract: Buildings provide an ideal platform for solar photovoltaics (PV) towards sustainable development goals, and the decision to invest in PV lies predominantly with building owners. Information delivery is critical for the diffusion of innovations, and this study aims to improve the quality of information for household PV investors in Sweden. A User Journey Mapping approach is applied with a combination of semi-structured interviews and a review of online solar calculators. The results show that despite a rapid growth in the quantity of information there is still a gap between demand and supply due to the lack of clarity and trustworthiness of information. This is clearly demonstrated in the review of online calculators, which show a high variance in results. Payback time, for example, ranged from 7 to 18 years for a single test case. The information gap can be closed by creating neutral, non-commercial online information sources that focus on transparency and education where household investors can validate supplier offers and analyses. The PV industry risks eroding trust in the market, which will likely slow adoption by the early majority and hinder sustainability goals. Highlights: User Journey Mapping is used to define the PV investment information gap. The growth of online information has not led to more informed investors. PV calculators suggest payback times of 7–18 years for a single sample home. The PV industry risks eroding trust by overpromising economic benefits. Non-commercial stakeholders should provide benchmarks and/or standards.